SIFAT DAN PENGARUH KOMPOSISI MOLEKUL UREA DAN FORMALDEHIDA PADA PEMBUATAN PEREKAT UREA FORMALDEHIDA TERHADAP KETEGUHAN REKAT KAYU LAPIS - Suwandi Kliwon (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This paper presents the result of a laboratory study on the properties of Urea formaldehyde resin manufactured with 5 molar ratio treatment of Urea and formaldehyde, and its effect on plywood glue shear strength. All composition of the Urea formaldehyde produced, and its physical properties (appearance, sticky matter, pH and viscosity) meet the Indonesian Indu.stry Standard for class 2a quality.The effects of Urea and formaldehyde molar ratio on glue shear strength of plywood were not significantly different. The average value of glue shear strength of Urea formaldehyde molar ratio 1 : 1,2 and 1 : 1,4 were meet the Indonesian Industry Standard.